Negotiating Faith: How Timorese Muslims Adapt Islamic Practices Through the 'Natoni' Ritual - Nobisa, Yahya Nikmat; Syaifuddin, Muhammad; Khozin, Khozin; Naitboho, Yanti Rosalina (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2025)
This article examines how the natoni ritual, an indigenous oral tradition of the Timorese people, is internalized within Islamic religious practices as a form of negotiation between faith and local tradition. Using a qualitative approach through ethnographic methods and in-depth interviews with traditional leaders, religious figures, and members of the Muslim community in Timor, this study explores the dynamics underlying this cultural-religious integration. The findings suggest that the incorporation of natoni into Islamic religious celebrations, such as welcoming guests during the Prophet Muhammad's birthday (Mawlid al-Nabi) and other communal religious events, serves as a symbolic mechanism for affirming local identity without compromising Islamic theological principles. Rather than merely serving as a cultural expression, natoni operates as a dialogical space that strengthens social cohesion and harmony between communities in Timor's multicultural society. This study further demonstrates the crucial role of traditional and religious leaders in reinterpreting natoni in a way that aligns with Islamic values ​​while preserving its legitimacy as a shared cultural heritage. These findings challenge the monolithic and ahistorical view of Islam in Indonesia, which portrays it as a homogeneous religious entity. This article contributes to the scholarly debate on religious localization and the indigenization of Islam by illustrating that religious practices are shaped not only by normative texts but also by ongoing social and cultural negotiations mediated by local actors. Thus, this study enriches discussions on the relationship between religion and culture and offers an alternative perspective on the realities of Islamic life in Indonesia's marginalized regions.